2022
DOI: 10.1126/scitranslmed.abj7521
|View full text |Cite
|
Sign up to set email alerts
|

Identification of driver genes for critical forms of COVID-19 in a deeply phenotyped young patient cohort

Abstract: The drivers of critical coronavirus disease 2019 (COVID-19) remain unknown. Given major confounding factors such as age and comorbidities, true mediators of this condition have remained elusive. We employed a multi-omics analysis combined with artificial intelligence in a young patient cohort where major comorbidities were excluded at the onset. The cohort included 47 "critical" (in the intensive care unit under mechanical ventilation) and 25 "non-critical" (in a non-critical care ward) patients with COVID-19 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 101 publications
(75 citation statements)
references
References 102 publications
1
74
0
Order By: Relevance
“…ADAM10 and ADAM17 thus both play crucial but distinct roles in SARS-CoV-2 infection. It has recently been reported that ADAM9 inhibition decreases SARS-CoV-2 infection in vitro [62]. Although the involvement of ADAM9 in viral entry is not clear, the results suggest that a group of metalloproteinases cooperate in the metalloproteinase pathway.…”
Section: Discussionmentioning
confidence: 80%
“…ADAM10 and ADAM17 thus both play crucial but distinct roles in SARS-CoV-2 infection. It has recently been reported that ADAM9 inhibition decreases SARS-CoV-2 infection in vitro [62]. Although the involvement of ADAM9 in viral entry is not clear, the results suggest that a group of metalloproteinases cooperate in the metalloproteinase pathway.…”
Section: Discussionmentioning
confidence: 80%
“…These auto-Abs were mostly found in men (95%), and half the patients carrying them were over the age of 65 yr ( Bastard et al, 2020b ). These findings were subsequently widely replicated in independent cohorts ( Abers et al, 2021 ; Acosta-Ampudia et al, 2021 ; Carapito et al, 2022 ; Chang et al, 2021 ; Chauvineau-Grenier et al, 2022 ; Goncalves et al, 2021 ; Koning et al, 2021 ; Raadsen et al, 2022 ; Solanich et al, 2021 ; Troya et al, 2021 ; van der Wijst et al, 2021 ; Vazquez et al, 2021 ; Wang et al, 2021 ; Zhang et al, 2022 ; Ziegler et al, 2021 ). Consistently, patients with APS-1 and preexisting anti–type I IFN auto-Abs were found to be at very high risk of severe disease upon SARS-CoV-2 infection ( Bastard et al, 2020b ; Beccuti et al, 2020 ; Carpino et al, 2021 ).…”
Section: Neutralizing Auto-abs Against Type I Ifns Underlie Severe Or...mentioning
confidence: 72%
“…S2’ priming causes membrane fusion between the viral particle and the plasma or endosomal membrane through interaction between the fusion peptide region and the cellular membrane, resulting in the release of viral RNA into the cytoplasm and its replication. We and others recently showed that host metalloproteinases are also involved in cell surface entry, independent of transmembrane protease, serine 2 (TMPRSS2) [21-23]. These results suggest that metalloproteinases act as the third host proteases for SARS-CoV-2 entry.…”
Section: Introductionmentioning
confidence: 88%